NKTR-102 Efficacy versus irinotecan in a mouse model of brain metastases of breast cancer. Issue 1 (December 2015) - Adkins, Chris; Nounou, Mohamed; Hye, Tanvirul; Mohammad, Afroz; Terrell-Hall, Tori; Mohan, Neel; Eldon, Michael; Hoch, Ute; Lockman, Paul
Abstract Background Brain metastases are an increasing problem in women with invasive breast cancer. Strategies designed to treat brain metastases of breast cancer, particularly chemotherapeutics such as irinotecan, demonstrate limited efficacy. Conventional irinotecan distributes poorly to brain metastases; therefore, NKTR-102, a PEGylated irinotecan conjugate should enhance irinotecan and its active metabolite SN38 exposure in brain metastases leading to brain tumor cytotoxicity. Methods Female nude mice were intracranially or intracardially implanted with human brain seeking breast cancer cells (MDA-MB-231Br) and dosed with irinotecan or NKTR-102 to determine plasma and tumor pharmacokinetics of irinotecan and SN38. Tumor burden and survival were evaluated in mice treated with vehicle, irinotecan (50 mg/kg), or NKTR-102 low and high doses (10 mg/kg, 50 mg/kg respectively). Results NKTR-102 penetrates the blood-tumor barrier and distributes to brain metastases. NKTR-102 increased and prolonged SN38 exposure (>20 ng/g for 168 h) versus conventional irinotecan (>1 ng/g for 4 h). Treatment with NKTR-102 extended survival time (from 35 days to 74 days) and increased overall survival for NKTR-102 low dose (30 % mice) and NKTR-102 high dose (50 % mice). Tumor burden decreased (37 % with 10 mg/kg NKTR-102 and 96 % with 50 mg/kg) and lesion sizes decreased (33 % with 10 mg/kg NKTR-102 and 83 % with 50 mg/kg NKTR-102) compared to conventional irinotecan treated animals. Conclusions Elevated and prolonged tumor SN38 exposure after NKTR-102 administration appears responsible for increased survival in this model of breast cancer brain metastasis. Further, SN38 concentrations observed in this study are clinically achieved with 145 mg/m2 NKTR-102, such as those used in the BEACON trial, underlining translational relevance of these results.